De novo lipogenesis in the differentiating human adipocyte can provide all fatty acids necessary for maturation - Collins, J; Neville, M; Pinnick, K; Hodson, L; Ruyter, B; Van Dijk, T; Reijngoud, D; Fielding, MD; Frayn, K (2011)
The primary products of de novo lipogenesis (DNL) are saturated fatty acids, which confer adverse cellular effects. Human adipocytes differentiated with no exogenous fat accumulated triacylglycerol (TG) in lipid droplets and differentiated normally. TG composition showed the products of DNL (saturated fatty acids from 12:0 to 18:0) together with unsaturated fatty acids (particularly 16:1n-7 and 18:1n-9) produced by elongation/desaturation. There was parallel upregulation of expression of genes involved in DNL and in fatty acid elongation and desaturation, suggesting coordinated control of expression. Enzyme products (desaturation ratios, elongation ratios, and total pathway flux) were also correlated with mRNA levels. We used 13C-labeled substrates to study the pathway of DNL. Glucose (5 mM or 17.5 mM in the medium) provided less than half the carbon used for DNL (42% and 47%, respectively). Glutamine (2 mM) provided 9-10%, depending upon glucose concentration. In contrast, glucose provided most (72%) of the carbon of TG-glycerol. Pathway analysis using mass isotopomer distribution analysis (MIDA) revealed that the pathway for conversion of glucose to palmitate is complex. DNL in human fat cells is tightly coupled with further modification of fatty acids to produce a range of saturated and unsaturated fatty acids consistent with normal maturation. Copyright © 2011 by the American Society for Biochemistry and Molecular Biology, Inc.